THE EFFECT OF FOOD PRICE ON TARGETED INFLATION IN SERBIA - Milanović, Milan; Ljubić, Marijana; Muminović, Saša (Economics of Agriculture, 2011)
The stability of market prices in the modern economy has gained primacy in the hierarchy of economic policy objectives. Thus, inflation targeting becomes a significant monetary policy instrument for a number of countries in the world. National Bank of Serbia, from mid-2006 onwards, has been implementing the monetary policy through the inflation targeting regime. Substantial geostrategic changes in the world, accompanied by economic and political turmoil, have caused abrupt increase in food and energy prices in recent years. Food prices in Serbia, have also had a pronounced dynamics. This paper focuses on a comparative review of trends in food prices globally and their impact on inflation, and provides a comparative analysis of multi-year trends in inflation and food prices in Serbia. The main objective of this paper is, in the context of indicated trends, to provide a analytical assessment of the impact of food prices on the targeted inflation (as a quality objective of central banks) in Serbia, as well as to define the instruments that could control such an inflationary impact.